Core-shell type catalyst as well as preparation method and application thereof

By coating I-doped BiOI with BiOI to form a core-shell heterojunction and combining it with piezoelectric properties, the problems of narrow spectral response range and full-time catalysis in the photocatalytic algae removal system were solved, achieving efficient algae cell inactivation and toxin degradation.

CN120771894AActive Publication Date: 2025-10-14HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511300274.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-12
Publication Date
2025-10-14
Estimated Expiration
2045-09-12

AI Technical Summary

Technical Problem

Existing photocatalytic algae removal systems have problems such as narrow spectral response range, fast recombination rate of photogenerated carriers, catalyst surface energy level mismatch, intermittent light dependence and limited transmission of reactive oxygen species, resulting in low quantum efficiency and inability to catalyze at all times.

Method used

A core-shell catalyst is used, with BiOI encapsulating I-doped BiOI to form a core-shell heterojunction. Combined with piezoelectric properties, it achieves all-weather algae removal. The close interface contact and large contact area of ​​the core-shell structure improve the transfer and separation of photogenerated charges, thereby enhancing the charge separation efficiency.

Benefits of technology

The photocatalytic reaction activity was significantly improved, algae cell inactivation and toxin degradation were achieved around the clock, and the stability of the catalyst and the algae removal effect were enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120771894A_ABST
    Figure CN120771894A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a core-shell type catalyst as well as a preparation method and application thereof, and the core-shell type catalyst comprises an inner core comprising I-doped BiOI; and the film layer comprises BiOI and is arranged on the surface of the inner core. The heterojunction of a core-shell structure formed by BiOI-coated I-doped BiOI not only can efficiently remove algae under illumination, but also can promote piezoelectric activation of persulfate without illumination, so that all-weather algae removal is realized; moreover, due to closer interface contact and larger contact area of the heterojunction in the core-shell structure, not only can the transfer and separation of photogenerated charges be improved, but also the stability can be ensured, tight protection is provided for active sites to resist severe environmental conditions, and the inactivation speed of the catalyst is effectively slowed down; meanwhile, due to the fact that BiOI has good piezoelectric performance, a heterojunction interface built-in electric field and a piezoelectric polarization electric field generated by the core-shell type catalyst can remarkably reduce carrier interface recombination so as to enhance charge separation efficiency, and photocatalytic reaction activity is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of catalytic algae removal, and in particular to a core-shell catalyst and a preparation method and application thereof. Background Art

[0002] As eutrophication in water bodies intensifies, the ecological crisis caused by cyanobacterial blooms is becoming increasingly severe. Explosive algal blooms not only reduce water clarity, deplete dissolved oxygen, and reduce biodiversity, but also release secondary pollutants such as microcystins and anabaxins, posing a direct threat to drinking water safety. Photocatalytic technology, with its green and energy-saving properties, uses sunlight to drive catalysts to produce reactive oxygen species, inactivating algal cells and degrading toxins. It is considered a revolutionary solution in environmental governance.

[0003] However, existing photocatalytic algae removal systems still face multiple technical bottlenecks: ① A narrow spectral response range: conventional semiconductor materials can only utilize less than 5% of the solar spectrum (ultraviolet band); ② The recombination rate of photogenerated carriers (picoseconds) is much faster than the migration rate (hundreds of picoseconds), resulting in low quantum efficiency; ③ The solvated water film on the catalyst surface causes energy level mismatch, hindering interfacial electron transfer; ④ The intermittent light dependence leads to catalytic failure at night and in rainy weather; ⑤ The transmission distance of reactive oxygen species in traditional non-contact catalysis is limited, making them easily quenched by the water matrix and difficult to reach algae cells. These bottlenecks severely restrict the large-scale application of photocatalytic technology in actual algal bloom control. There is an urgent need to develop new photocatalytic systems with broad spectral response, efficient carrier separation, and full-time catalytic algae removal. Summary of the Invention

[0004] The embodiments of the present application provide a core-shell catalyst and its preparation method and application, aiming to improve the problems of low photon utilization rate, low catalytic reaction activity and inability to catalyze full-time in existing photocatalysts.

[0005] In order to solve the above problems, this application is implemented through the following technical solutions: This application proposes a core-shell catalyst, comprising: core, including I-doped BiOI; A film layer, including BiOI, is disposed on the surface of the core.

[0006] In the core-shell catalyst provided in the embodiments of the present application, the core-shell heterojunction formed by BiOI-coated I-doped BiOI can not only efficiently remove algae under light, but also promote piezoelectric activation of persulfate in the absence of light, thereby achieving all-weather algae removal; moreover, due to the closer interface contact and larger contact area of ​​the heterojunction in the core-shell structure, it can not only improve the transfer and separation of photogenerated charges, but also ensure stability, provide strict protection for the active sites to withstand harsh environmental conditions, and effectively slow down the deactivation rate of the catalyst; at the same time, due to the good piezoelectric properties of BiOI, the built-in electric field and piezoelectric polarization electric field of the heterojunction interface generated by the core-shell catalyst can significantly reduce carrier interfacial recombination to enhance charge separation efficiency, thereby significantly improving the photocatalytic reaction activity; in addition, the material can form a complex with algal blooms, thereby achieving in situ algae removal and significantly improving the algae removal effect.

[0007] Furthermore, in the core-shell catalyst, the catalyst is spherical.

[0008] Furthermore, in the core-shell catalyst, the diameter of the catalyst is 0.8-2 μm.

[0009] Furthermore, in the core-shell catalyst, the diameter of the core is 0.1-0.75 μm, and the thickness of the membrane layer is 0.1-0.5 μm.

[0010] Furthermore, the core-shell catalyst is prepared in situ by a one-pot method.

[0011] This application proposes a method for preparing a core-shell catalyst, comprising: Bismuth nitrate is dissolved in ethylene glycol methyl ether to form a first solution; dissolving potassium iodide in ethylene glycol methyl ether to form a second solution; Under stirring conditions, the second solution is added dropwise to the first solution, and then sealed and heated for reaction, and then cooled, washed and dried to obtain a core-shell catalyst, wherein the heating reaction temperature is 120°C to 200°C and the time is 5 h to 20 h.

[0012] The preparation method provided in the embodiment of the present application first prepares a KI ethylene glycol methyl ether solution and a bismuth nitrate ethylene glycol methyl ether solution as an I ionic liquid, and utilizes the miscibility of KI and bismuth nitrate in ethylene glycol methyl ether. When the KI solution is added dropwise to the bismuth nitrate ethylene glycol methyl ether solution, an emulsion is formed under stirring, achieving a droplet domain similar to that in a traditional oil-in-ionic liquid. The micro-sized KI microemulsion is filled with Bi 3+ The micro-reaction chamber is formed by the ethylene glycol methyl ether, and under heating conditions, Bi 3+The ions react with the I ions on the microemulsion interface to form a BiOI shell; at the same time, a large amount of KI ethylene glycol methyl ether solution inside the microemulsion reacts with a small amount of Bi(NO3)3·5H2O ethylene glycol methyl ether solution that infiltrates to form I-rich BiOI, obtaining a core-shell catalyst with BiOI coating I-doped BiOI.

[0013] Furthermore, in the preparation method, the reaction temperature is 160° C. and the reaction time is 12 h.

[0014] Furthermore, in the preparation method, the concentration of bismuth nitrate is 0.005-0.5 mmol / mL; and in the second solution, the concentration of potassium iodide is 0.005-0.5 mmol / mL.

[0015] Furthermore, in the preparation method, during the process of dropwise adding the second solution to the first solution, the molar ratio of the bismuth nitrate to the potassium iodide is controlled to be 1:1.

[0016] Furthermore, in the preparation method, during the process of adding the second solution dropwise to the first solution, the stirring speed is controlled to be 200 r / min to 1000 r / min and the stirring time is 5 to 20 min; and / or In the process of dissolving bismuth nitrate in ethylene glycol methyl ether, controlling the stirring speed to be 100 r / min to 500 r / min and the stirring time to be 25 to 60 min; and / or In the process of dissolving potassium iodide in ethylene glycol methyl ether, the stirring speed is controlled to be 100 r / min~500 r / min, and the stirring time is 5~60 min.

[0017] Furthermore, in the preparation method, the drying temperature is less than or equal to 80°C.

[0018] The present application also proposes an application of the core-shell catalyst, wherein the core-shell catalyst is used to inactivate algae. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the structure of the core-shell catalyst provided in the examples of the present application; Figure 2 This is a flow chart of a method for preparing a core-shell catalyst provided in an embodiment of the present application; Figure 3 This is an electron microscope test image of the core-shell catalyst in the embodiment of the present application; Figure 4 This is the XRD test pattern of the core-shell catalyst in the embodiment of the present application; Figure 5This is the XPS test graph of the core-shell catalyst in the embodiment of the present application; Figure 6 This is a KPFM test diagram of the core-shell catalyst in the embodiment of the present application; Figure 7 This is a UV diffuse reflectance test diagram of the core-shell catalyst in the embodiment of the present application; Figure 8 1 is a transient photocurrent response and impedance test diagram of the core-shell catalyst in the embodiment of the present application; Figure 9 This is a piezoelectric photocatalytic activity test diagram of the core-shell catalyst in the embodiment of the present application; Figure 10 This is a graph showing the in-situ all-weather degradation performance test of the core-shell catalyst in the embodiment of the present application; Figure 11 This is a test diagram of the cycle performance of the core-shell catalyst in the embodiment of the present application; Figure 12 This is an in-situ infrared spectrum test and in-situ Raman spectrum test diagram of the core-shell catalyst in the embodiment of the present application; Figure 13 is the scanning electron microscopy image of algal cell morphology under different treatment durations; Figure 14 This is a quenching experiment test diagram in the embodiment of this application. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects solved by this application more clearly understood, this application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.

[0021] As eutrophication in water bodies intensifies, the ecological crisis caused by cyanobacterial blooms is becoming increasingly severe. Photocatalytic technology, with its green and energy-saving properties, uses sunlight to drive catalysts to produce reactive oxygen species, thereby inactivating algal cells and degrading toxins. It is considered an innovative solution in environmental governance.

[0022] However, existing photocatalytic algae removal systems still face multiple technical bottlenecks: ① A narrow spectral response range: conventional semiconductor materials can only utilize less than 5% of the solar spectrum (ultraviolet band); ② Charge carrier migration from the bulk to the catalytic active sites on the catalyst surface requires hundreds of picoseconds, while charge recombination in the bulk only takes a few picoseconds. This low mobility leads to a high recombination rate, resulting in low quantum efficiency; ③ The solvated water film on the catalyst surface causes energy level mismatch, hindering interfacial electron transfer; ④ Intermittent light dependence leads to catalytic failure at night and in rainy weather; ⑤ The transmission distance of reactive oxygen species in traditional non-contact catalysis is limited, making them easily quenched by the water matrix and difficult to reach algae cells. These bottlenecks severely restrict the large-scale application of photocatalytic technology in actual algal bloom control. There is an urgent need to develop new photocatalytic systems with broad spectral response, efficient charge carrier separation, and full-time catalytic algae removal.

[0023] The applicant found that in order to address the above-mentioned problems of photocatalytic algae removal, if only heteroatom doping is used to construct a semiconductor heterojunction, the built-in electric field will have a low efficiency in promoting carrier separation, which in turn leads to low algae removal efficiency. The applicant also found that mechanical disturbances of water flow are common in areas with severe algal bloom pollution, and piezoelectric materials can use the mechanical disturbances of water flow to generate localized polarization electric fields, thereby effectively promoting the migration and separation of carriers. Compared with traditional methods such as defect modification and heteroatom doping, photocatalytic coupled piezoelectric materials can significantly inhibit carrier recombination. In addition, the energy band bending under the action of piezoelectric potential can increase the valence band potential, reduce the energy required for electron transitions, and thus improve spectral utilization. Furthermore, the polarization electric field generated by piezoelectricity can promote the activation of persulfate, and even in the dark night, a variety of reactive oxygen species can be continuously produced, achieving all-weather inactivation of experimental algal blooms.

[0024] However, traditional piezoelectric materials still have problems such as low mechanical force sensitivity, low energy conversion efficiency and narrow spectral absorption. For example: current piezoelectric catalytic reactions are generally driven by high-frequency ultrasound, and the utilization rate of low-frequency natural energy such as water flow is low; the piezoelectric coefficient of non-lead-based environmentally friendly piezoelectric materials is low; common single piezoelectric materials (molybdenum disulfide MoS2, zinc oxide ZnO, etc.) have a wide band gap and limited absorption of visible light; persulfate activation requires matching the electronic structure of the material, thereby promoting the generation of reactive oxygen species.

[0025] Based on the above findings, in order to solve the problems of the existing photocatalyst having a narrow spectral response range, low catalytic reaction activity and inability to catalyze algae removal at all times, the embodiment of the present application provides a core-shell catalyst 100, such as Figure 1 As shown in FIG2 , the material 100 includes a core 11 including I-doped BiOI; and a film layer 12 including BiOI, which is disposed on the surface of the core 11 .

[0026] In the core-shell catalyst provided in the embodiments of the present application, a core-shell heterojunction structure is formed by BiOI-coated I-doped BiOI (IBiOI). This not only combines the chemical composition, electronic structure, and micromorphology of the piezoelectric material and the photocatalytic material to promote piezoelectric activation of persulfate in the absence of light, thereby achieving all-weather algae removal. Moreover, due to the closer interface contact and larger contact area of ​​the heterojunction in the core-shell structure, it can not only significantly improve the transfer and separation of photogenerated charges, but also ensure stability, providing strict protection for the active sites to withstand harsh environmental conditions, thereby effectively slowing the deactivation rate of the catalyst. At the same time, due to the good piezoelectric properties of BiOI, the built-in electric field and piezoelectric polarization electric field generated by the heterojunction interface of the core-shell catalyst can significantly reduce carrier interfacial recombination to enhance charge separation efficiency, thereby significantly improving the photocatalytic reaction activity. In addition, the material can form a complex with algal blooms, thereby achieving in situ algae removal and significantly improving the algae removal effect.

[0027] Alternatively, given that the catalyst can utilize solar energy and mechanical energy to generate strong oxidative reactive oxygen species, the catalyst can also be used to degrade pollutants such as phenol, bisphenol A, and antibiotics; and can also be used to inactivate pathogenic microorganisms.

[0028] Optionally, in one embodiment, the core-shell catalyst is spherical as a whole, which not only makes the heterojunction formed therein have a tighter interface contact and a larger contact area, thereby improving the photogenerated charge transfer and separation, but also makes the structure more stable, thereby effectively slowing down the deactivation rate of the catalyst.

[0029] Optionally, in one embodiment, the diameter of the core-shell catalyst is 0.8-2 μm. At this particle size, the catalyst particles not only have a larger specific surface area, but are also more evenly distributed and less likely to agglomerate.

[0030] Optionally, in a specific embodiment, the diameter of the core of the core-shell catalyst is 0.25-0.75 μm, and the thickness of the membrane layer is 0.1-0.5 μm, which can effectively take into account the structural strength and catalytic performance of the material and more reasonably match BiOI and IBiOI.

[0031] Among them, during the preparation process of the core-shell catalyst, the size of the droplets in the system, the concentrations of KI and bismuth nitrate, as well as the temperature, stirring rate, etc. can be adjusted to control the size ratio of the membrane layer and the core of the prepared catalyst.

[0032] The present invention provides a method for preparing a core-shell catalyst. Figure 2 As shown, the method includes steps 201 to 203: Step 201: dissolving bismuth nitrate in ethylene glycol methyl ether to form a first solution; Step 202: dissolving potassium iodide in ethylene glycol methyl ether to form a second solution; Step 202: under stirring, dropwise add the second solution to the first solution, then seal and heat for reaction, then cool, wash and dry to obtain a core-shell catalyst, wherein the heating reaction temperature is 120° C. to 200° C. and the time is 5 h to 20 h.

[0033] In the embodiment of the present application, a KI glycol methyl ether solution containing I ionic liquid and a Bi(NO3)3∙5H2O glycol methyl ether solution containing Bi ionic liquid are first configured, and the limited miscibility of the KI ionic liquid and the Bi(NO3)3∙5H2O ionic liquid in glycol methyl ether is utilized to form an emulsion under stirring, realizing a droplet domain similar to that in the traditional oil-in-oil ionic liquid; when the KI ionic liquid is added dropwise to the bismuth nitrate glycol methyl ether solution, the tiny-sized KI microemulsion is filled with Bi 3+ The micro-reaction chamber is formed by the ethylene glycol methyl ether, and under heating conditions, Bi 3+ The ions react with the I ions on the microemulsion interface to form a BiOI shell; at the same time, the KI ethylene glycol methyl ether solution inside the microemulsion reacts with a small amount of Bi(NO3)3·5H2O ethylene glycol methyl ether solution that infiltrates to form I-doped BiOI (IBiOI), obtaining a BiOI-coated IBiOI core-shell catalyst.

[0034] In step 201, stirring is performed while dissolving bismuth nitrate in ethylene glycol methyl ether to promote dissolution of the bismuth nitrate. Optionally, the bismuth nitrate may be bismuth nitrate pentahydrate, and the stirring speed is controlled to be 100 r / min to 500 r / min, and the stirring time is 25 to 60 min, which can effectively promote the dissolution of the bismuth nitrate while preventing excessive oxygen from entering.

[0035] In the above step 201, the stirring speed can be one of 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min or any two of the range values, and the stirring time can be one of 25 min, 30 min, 40 min, 50 min, 60 min or any two of the range values.

[0036] Optionally, in the above-mentioned first solution, the concentration of bismuth nitrate can be 0.01~0.2 mmol / mL, for example, it can be one or any two range values ​​of 0.01 mmol / mL, 0.02 mmol / mL, 0.05 mmol / mL, 0.8 mmol / mL, 0.1 mmol / mL, 0.15 mmol / mL, 0.2 mmol / mL. Its concentration is moderate, which is convenient for contact reaction with KI, thereby improving the piezoelectric photocatalytic performance of the product, and avoiding the precipitation of bismuth nitrate and causing material waste.

[0037] For example, 0.3 mmol Bi(NO3)3∙5H2O can be dissolved in 30 mL of ethylene glycol methyl ether while stirring, wherein the stirring speed is controlled at 300 r / min and the stirring time is controlled at 40 min, so that the subsequently prepared BiOI has better piezoelectric photocatalytic performance.

[0038] In step 202, stirring is performed while dissolving KI in ethylene glycol methyl ether to promote dissolution of KI. Optionally, in the above step, the stirring speed is controlled to be 100 r / min to 500 r / min, and the stirring time is 5 to 60 min. This can effectively promote the dissolution of bismuth nitrate while preventing excessive oxygen from incorporating and causing oxidation of KI.

[0039] In the above step 201, the stirring speed can be one of 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min or any two of the range values, and the stirring time can be one of 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min or any two of the range values.

[0040] Optionally, in the above-mentioned first solution, the concentration of potassium iodide can be 0.01~0.2 mmol / mL, for example, it can be one or any two range values ​​of 0.01 mmol / mL, 0.02 mmol / mL, 0.05 mmol / mL, 0.8 mmol / mL, 0.1 mmol / mL, 0.15 mmol / mL, 0.2 mmol / mL. Its concentration is moderate, which is convenient for contact reaction with bismuth nitrate, thereby improving the piezoelectric photocatalytic performance of the product, and avoiding the precipitation of potassium iodide and causing material waste.

[0041] For example, 0.3 mmol KI can be dissolved in 30 mL of ethylene glycol methyl ether under stirring, wherein the stirring speed is controlled to be 300 r / min and the stirring time is controlled to be 40 min, so that the subsequently prepared BiOI has better piezoelectric photocatalytic performance.

[0042] In the above step 203, the second solution is slowly added dropwise to the first solution under stirring conditions, so that the micro-sized KI microemulsion is filled with Bi 3+ The micro-reaction chamber is then sealed and heated at 120°C to 200°C. 3+ The ions react with the I ions on the microemulsion interface to form a BiOI shell. At the same time, the KI ethylene glycol methyl ether solution inside the microemulsion reacts with a small amount of Bi(NO3)3·5H2O ethylene glycol methyl ether solution that has infiltrated to form IBiOI, obtaining a BiOI-coated IBiOI core-shell catalyst. The final product can then be obtained by cooling, washing, and drying.

[0043] Optionally, in one embodiment, during the process of adding the second solution dropwise to the first solution, the stirring speed is controlled to be 200 r / min to 1000 r / min and the stirring time is 5 to 20 min; and / or The reaction temperature may be within the range of one or any two of 120°C, 150°C, 160°C, 170°C, 180°C, and 200°C, and the reaction time may be within the range of one or any two of 5 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, and 20 h.

[0044] Alternatively, in one embodiment, the reaction temperature is controlled to be 160° C. and the reaction time is controlled to be 12 h.

[0045] Optionally, in one embodiment, during the process of adding the second solution dropwise to the first solution, the molar ratio of bismuth nitrate to potassium iodide is controlled to be 1:1, so that the energy levels of BiOI and IBiOI in the formed core-shell structure product are reasonably matched and the piezoelectric photocatalytic performance is particularly good.

[0046] In the above step 203, after the reaction product is cooled to room temperature, it can be rinsed with deionized water and ethanol for multiple times, and then dried at 80° C. or less to prevent the product from being oxidized.

[0047] Alternatively, in one embodiment, the product can be dried in a vacuum drying oven at 60°C.

[0048] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention is further described below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0049] The present invention is described in detail below by way of examples.

[0050] Example 1 (1) Under stirring conditions, 0.3 mmol Bi(NO3)3∙5H2O was dissolved in 30 mL of ethylene glycol methyl ether to obtain a first solution; wherein the stirring speed was controlled at 300 r / min and the stirring time was controlled at 40 min; (2) Under stirring conditions, 0.3 mmol KI was dissolved in 30 mL ethylene glycol methyl ether to obtain a second solution; wherein the stirring speed was controlled at 300 r / min and the stirring time was controlled at 40 min; (3) Under stirring conditions, the second solution was added dropwise to the first solution, which was then sealed and heated for reaction. The solution was then cooled, washed, and dried in a vacuum drying oven at 60°C to obtain a core-shell catalyst. The reaction temperature was 160°C and the reaction time was 12 h.

[0051] Examples 2 to 6 The difference between Examples 2 to 6 and Example 1 is that in step (3), the stirring speed is adjusted to 200 r / min, 400 r / min, 600 r / min, 800 r / min, and 1000 r / min, respectively.

[0052] Test Example 1 The catalyst prepared in Example 1 was tested by scanning electron microscopy. Figure 3 As shown in (a). Figure 3 As can be seen in (a), the prepared catalyst has a spherical nanostructure with obvious epitaxial wrinkles.

[0053] The catalyst prepared in Example 1 was tested by high-angle annular dark field scanning transmission electron microscopy. Figure 3 As shown in (b) to (f), Figure 3 (b)-(c) are high-angle annular dark-field scanning transmission electron microscopy images, and (d)-(f) are energy dispersive spectroscopy (EDS) elemental distribution maps corresponding to Bi, I, and O. It can be seen that Bi, I, and O are distributed in the outer layer of the spherical particles, while the inner layer is mainly IBiOI, indicating that the catalyst prepared in Example 1 is a spherical nanomaterial with a core-shell structure.

[0054] Test Example 2 The catalyst prepared in Example 1 was subjected to XRD test, and the results were as follows: Figure 4 As shown, it can be seen that compared with the BiOI (PDF#10-0445) standard card, the XRD peaks of the prepared catalyst showed obvious (102), (110), (004), and (212) crystal planes, indicating that BiOI was successfully prepared. The XRD peak of BiOI shifted to high angles, further indicating that it may have a core-shell structure.

[0055] Test Example 3 The catalyst prepared in Example 1, the algae-catalyst mixture and the algae were respectively tested by XPS, and the results are shown in Figs. (a)-(c) respectively. Figure 5 The algae-catalyst mixture was prepared by mixing the catalyst with the algae solution and stirring for 20 minutes, then freezing the mixture and placing it in a freeze-drying box for 48 hours.

[0056] wherein, Figure 5 In Fig. (a), the Bi 4f peaks at 160.3 eV and 165.6 eV in BiOI are respectively attributed to Bi 4f 7 / 2 and Bi4f 5 / 2 (Bi 3+ ); from Figure 5 As can be seen from Fig. (b), after mixing with algae, the Bi 4f 7 / 2 and Bi 4f 5 / 2 peaks of BiOI respectively shift to 159.0 and 164.3 eV, which may be due to the coordination of Bi 3 ⁺ on the surface of BiOI with the abundant functional groups such as carboxyl (-COOH), hydroxyl (-OH) and amino (-NH2) on the surface of algae, forming Bi-O-C or Bi-N complex structure; Figure 5 In Fig. (c), there is also a significant I 3d peak shift. The I 3d 5 / 2 (619.7 eV) and I 3d 3 / 2 (631.2 eV) of BiOI shift to 619.9 eV and 630.5 eV after mixing with algae; in addition, in O 1s, 530.7 eV and 532 eV are respectively Bi-O and O-H bonds. In summary, the core-shell catalyst is successfully prepared, and the catalyst can coordinate with the abundant functional groups on the surface of algae.

[0057] Test Example 4 The catalyst prepared in Example 1 was tested by KPFM, and the morphology image, amplitude image, phase image and butterfly-shaped displacement-voltage curve are shown in Figs. (a)-(d) respectively. Figure 6

[0058] Among them, the image contrast of the morphology image and the amplitude image and the phase image is obvious, indicating that the catalyst is a piezoelectric material; at the same time, combined with the typical butterfly-shaped displacement-voltage curve in Fig. (d), it is further indicated that the material has piezoelectric properties. By calculating the slope of the displacement-voltage curve, the maximum effective piezoelectric coefficient d33 of the sample is 1 mV / V. In summary, the prepared catalyst is a piezoelectric material and has good piezoelectric properties. Figure 6

[0059] Test Example 5 ​​The catalyst prepared in Example 1 was subjected to UV diffuse reflectance test. The UV diffuse reflectance spectrum and band gap width were as follows: Figure 7 The band gap is calculated based on the UV diffuse reflectance spectrum using the following formula: αhν = A(E g -hν) n / 2 , where α, h, ν, A and E g are the absorption coefficient, Planck constant, incident light frequency, constant, and bandgap width, respectively. In this equation, for direct bandgap semiconductors, n is equal to 1.

[0060] pass Figure 7 It can be seen that the absorption edge of the prepared catalyst is about 545 nm, indicating that the material has good visible light absorption performance and a band gap of 1.96 eV.

[0061] Test Example 6 The catalyst prepared in Example 1 was subjected to transient photocurrent response test and impedance test, and the results were as follows: Figure 8 As shown in (a) and (b).

[0062] The test method is as follows: Nafion solution (5.0 wt%, 0.1 mL) and BiOI (10 mg) were mixed with ethanol (1 mL) and ultrasonically dispersed for 3 h to obtain a suspension. 20 μL of the suspension was dropwise applied to a conductive glass surface and dried at 60°C for 8 h to obtain an electrode sheet. Photocurrent and impedance measurements were performed using an electrochemical workstation (Chenhua CHI660E, Shanghai) equipped with a conventional three-electrode configuration, using a 300 W xenon lamp as the light source and 0.1 M Na₂SO₄ solution as the electrolyte. The addition of 0.01 mmol / L PMS resulted in a BiOI / PMS system, while the addition of 0.01 mmol / L PMS resulted in a BiOI system.

[0063] pass Figure 8 It can be seen that the prepared catalyst can generate a significant photocurrent under light, indicating that the catalyst has a good photoelectric effect. In addition, compared with the BiOI system, the catalyst / peroxymonosulfate system (BiOI / PMS system) has a stronger photocurrent, which indicates that BiOI promotes the activation of PMS under light.

[0064] Test Example 7 The catalysts prepared in each example were tested for piezoelectric photocatalytic activity, and the results were as follows: Figure 9 The specific test method is as follows: The catalyst was placed in a piezoelectric photoreaction device to perform an experiment on the degradation of Microcystis aeruginosa. During the photocatalytic reaction, an LED lamp was used as the light source. 40 mL of algae suspension was used. The reactor contained (0.5 g / L) or no catalyst. The light source was turned on / off (20 W / m2 ), the reactor was placed under ultrasound / no ultrasound, and with / without the addition of peroxymonosulfate.

[0065] According to the different reaction conditions in the above experiments: presence / absence of catalyst (BiOI), light source on / off (Vis), presence / absence of ultrasound (US), and addition / non-addition of permonosulfate (PMS), the following reaction systems can be obtained: permonosulfate (PMS) system; ultrasound / visible light (US / Vis) system; permonosulfate / ultrasound (PMS / US) system; permonosulfate / visible light (PMS / Vis) system; permonosulfate / ultrasound / visible light (PMS / US / Vis) system; catalyst / permonosulfate (BiOI / PMS) system; catalyst / ultrasound / visible light (BiOI / US / Vis) system; catalyst / permonosulfate / ultrasound (BiOI / PMS / US) system; catalyst / permonosulfate / visible light (BiOI / PMS / Vis) system.

[0066] At preset intervals, 8 mL of the reaction solution was taken to measure its chlorophyll a content. A 0.45 μm filter membrane was placed on the filtration instrument, and then 8 mL of the sample was filtered. The filter membrane was placed in a test tube and frozen for 12 h. After that, the test tube was taken out and 8 mL of 90% acetone solution was added. A small amount of magnesium carbonate powder was added to protect the chlorophyll from being destroyed. The cells were disrupted by an ultrasonic cell disruptor (ultrasonication time 3 s, interval time 2 s) for 3 min, and the sample was treated at a speed of 4500 r / min for 10 min. The supernatant was taken and 90% acetone was used as a reference. The OD value was calculated. 630 ,OD 647 ,OD 664 and OD 750 Determine the content of chlorophyll a. The calculation formula is as follows:

[0067] Where: OD 630 ,OD 647 ,OD 664 ,OD 750 are the absorbance values ​​of the samples at wavelengths of 630 nm, 647 nm, 664 nm, and 750 nm, respectively; V1 is the sample volume, mL; V2 is the volume of 90% acetone, mL; The removal efficiency of Microcystis aeruginosa was calculated as C / C0, where C0 and C were the chlorophyll a contents at 0 and t min, respectively.

[0068] Depend on Figure 9As shown in (a), the catalyst in Example 1 has a better piezoelectric photocatalytic algae removal effect, and the chlorophyll of algae cells can be significantly destroyed under the action of ultrasound and piezoelectricity, indicating that the BiOI / US / Vis system can achieve 100% inactivation of algae cells, which is much higher than the catalysts prepared in other examples. Figure 9 As shown in (b), the US / Vis system, the PMS / US system, and the PMS / US / Vis system alone will not cause the death of algae, which indicates that the core-shell structure catalyst prepared by optimizing the experimental preparation method has a better algae removal effect.

[0069] Test Example 8 The catalyst prepared in Example 1 was subjected to an in-situ all-weather degradation performance test, and the results were as follows: Figure 10 As shown, the specific test method is consistent with that of Test Example 7, except that 0.01 mM permonosulfate (PMS) is added as an oxidant in this test example.

[0070] Depend on Figure 10 The BiOI / PMS / US / Vis system demonstrated superior algae removal performance, demonstrating the BiOI material's excellent photocatalytic and piezoelectric properties. Mechanical action generates a polarized electric field, promoting charge carrier separation and generating a large number of reactive oxygen species, resulting in efficient algae inactivation. The BiOI / PMS / Vis system inactivated 90% of Microcystis aeruginosa in 150 minutes, demonstrating the core-shell BiOI catalyst's excellent photocatalytic performance and its ability to generate a large number of reactive oxygen species under light, effectively inactivating algal cells. At the same time, the BiOI / PMS / US / Vis system has a higher algae removal efficiency, indicating that under the action of piezoelectricity and photocatalysis, PMS activation can be promoted to generate reactive oxygen species such as sulfate radicals and hydroxyl radicals, thereby promoting the removal of algal blooms. In addition, the BiOI / PMS / US system can inactivate 60% of algae in 150 minutes, indicating that the prepared catalyst can use the mechanical disturbance of water flow to generate a polarized electric field on a dark night, generating a large number of reactive oxygen species to inactivate algal cells, that is, the catalyst can achieve all-weather in-situ inactivation of algal blooms.

[0071] Test Example 9 The catalyst prepared in Example 1 was subjected to a cycle performance test, and the results were as follows: Figure 11 The specific test method is as follows: After the first degradation reaction is completed, the catalyst is separated from the solution by filtration, and the filtered catalyst is washed with deionized water and ethanol, and then dried in a freeze dryer for 48 hours for use; the above-mentioned spare materials are used to carry out a second degradation reaction. Except for the materials, the other reaction conditions are consistent with the first one; after the second reaction is completed, the above steps are repeated to carry out the third, fourth and fifth degradation experiments.

[0072] Depend on Figure 11It can be seen that the BiOI / PMS / US / Vis system has good cyclic stability. After 5 cycles, the algal cells can still be completely inactivated within 150 min, indicating that the material has good cyclic stability.

[0073] Test Example 10 The catalyst prepared in Example 1 was subjected to in-situ infrared spectroscopy and in-situ Raman spectroscopy tests, and the results were as follows: Figure 12 As shown in (a) to (b), the specific test method is as follows: In situ Raman testing: A 532 nm laser confocal Raman spectrometer was used to study the surface chemical changes of the catalyst during the PMS activation process. Specifically, 10 mg of the catalyst was loaded onto a glass slide and pressed into a thin slice about 1 mm thick. PMS solution (0.01-2 mmol / L) was then dripped onto the slice. The surface chemical changes of the catalyst during the PMS activation process were studied using a 532 nm laser confocal Raman spectrometer ... -1 Scan within range.

[0074] In situ infrared testing: Fourier transform infrared spectrometer was used to study the changes in the surface functional groups of the catalyst during the PMS activation process. Specifically, 10 mg of catalyst was added to the infrared spectrometer test bench, PMS solution (0.01-2 mmol / L) was added dropwise, and then the surface functional groups of the catalyst were measured at 500-2500 cm -1 Scan within range.

[0075] Depend on Figure 12 As can be seen in (a), compared with the system without PMS, the Bi-O bond of BiOI disappears after adding PMS, which indicates that PMS can react with Bi on BiOI and further generate reactive oxygen species, allowing BiOI to continuously remove algae in the dark night.

[0076] Depend on Figure 12 As can be seen in (b), compared with the system without PMS, the Bi-I bond of BiOI shifts significantly after adding PMS; in addition, the OO bond peak of PMS becomes broader. Combined with the in situ infrared results, it shows that PMS can react with the Bi of BiOI in the absence of light, allowing BiOI to continue to remove algae in the dark night.

[0077] Test Example 11 The catalyst prepared in Example 1 was tested for algae removal by the BiOI / PMS / US / Vis system for 10 min, 20 min and 30 min, and the PMS / US / Vis system was tested for algae removal for 1.5 h as a control group. The algae cell morphology was observed by biological SEM. The results were as follows: Figure 13 As shown in (a) to (d).

[0078] Depend on Figure 13It can be seen that in the BiOI / PMS / US / Vis system, the algal cells gradually shrank and damaged as the reaction progressed, while in the control group PMS / US / Vis system, the algal cells remained plump, indicating that the BiOI / PMS / US / Vis system can significantly damage the algal cell membrane, thereby leading to the damage and death of the algal cells.

[0079] Test Example 12 The catalyst prepared in Example 1 was subjected to a quenching experiment to investigate the main active oxygen species of the all-weather algae removal system under light. The test results are as follows: Figure 14 As shown, the specific test method is as follows: The experimental method is consistent with Test Example 8, except that different amounts of quenchers are added to the system before the reaction starts, and ethanol (Ethanol) is used to quench sulfate radicals and hydroxyl radicals, disodium ethylenediaminetetraacetic acid (EDTA-2Na, 1 mmol / L) is used to quench holes, furfuryl alcohol (FFA, 1 mmol / L) is used to quench singlet oxygen, tert-butyl alcohol (TBA, 3 mmol / L) is used to quench hydroxyl radicals, and para-benzoquinone (BQ, 3 mmol / L) is used to quench superoxide radicals.

[0080] Depend on Figure 14 After the addition of BQ, the BiOI / PMS / US / Vis system only removed 10% of the algae (150 min). Under the quenching effect of FFA, the algae removal efficiency of the BiOI / PMS / US / Vis system decreased to 80%. EDTA-2Na also significantly inhibited the inactivation of algal blooms, with the BiOI / PMS / US / Vis system only inactivating 70% of the algae. These results indicate that the main reactive oxygen species in the BiOI / PMS / US / Vis system are superoxide radicals, singlet oxygen, and holes, indicating that the prepared catalyst can efficiently absorb photons, causing valence band electrons to transition to the conduction band and generate holes in the valence band. Simultaneously, the built-in electric field of the core-shell structure and the polarization field generated by piezoelectricity promote carrier separation, and the photogenerated electrons further activate the surface-adsorbed PMS and oxygen to generate superoxide radicals and singlet oxygen.

[0081] In summary, in the core-shell catalyst provided in the embodiment of the present application, the core-shell structure heterojunction formed by BiOI-coated I-doped BiOI not only integrates the chemical composition, electronic structure and micromorphology of the piezoelectric material and the photocatalytic material, but also promotes the piezoelectric activation of persulfate in the absence of light, thereby achieving all-weather algae removal; moreover, due to the closer interface contact and larger contact area of ​​the heterojunction in the core-shell structure, it can not only improve the photogenerated charge transfer and separation, but also ensure stability, provide strict protection for the active sites to withstand harsh environmental conditions, and effectively slow down the deactivation rate of the catalyst; at the same time, due to the good piezoelectric properties of BiOI, the built-in electric field and piezoelectric polarization electric field of the heterojunction interface generated by the core-shell catalyst can significantly reduce the carrier interface recombination to enhance the charge separation efficiency, thereby significantly improving the photocatalytic reaction activity; in addition, the material can form a complex with the algae bloom, thereby achieving in situ algae removal and significantly improving the algae removal effect.

[0082] Terminology In this application, a plurality refers to two or more.

[0083] The terms "first," "second," "third," "fourth," etc. (if any) in this application are used to distinguish similar objects and are not necessarily used to describe a particular sequential order.

[0084] The term "and / or" in this application simply describes an association between related objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this application generally indicates that the related objects are in an "or" relationship.

[0085] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, a statement that the method includes steps A and B indicates that the method may include steps A and B performed sequentially, or steps B and A performed sequentially. For example, a statement that the method may also include step C indicates that step C may be added to the method in any order, for example, the method may include steps A, B, and C, or steps A, C, and B, or steps C, A, and B, etc.

[0086] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A core-shell catalyst, characterized in that include: core, including I-doped BiOI; A film layer, including BiOI, is disposed on the surface of the core.

2. The core-shell catalyst according to claim 1, characterized in that The catalyst is spherical.

3. The core-shell catalyst according to claim 1, characterized in that The diameter of the catalyst is 0.8-2 μm.

4. The core-shell catalyst according to claim 3, characterized in that The diameter of the core is 0.25-0.75 μm, and the thickness of the film layer is 0.1-0.5 μm.

5. A method for preparing a core-shell catalyst, characterized in that: include: dissolving bismuth nitrate in ethylene glycol methyl ether to form a first solution; dissolving potassium iodide in ethylene glycol methyl ether to form a second solution; Under stirring conditions, the second solution is added dropwise to the first solution, then sealed and heated for reaction, and then cooled, washed and dried to obtain a core-shell catalyst, wherein the heating reaction temperature is 120°C~200°C and the time is 5 h~20 h.

6. The preparation method according to claim 5, characterized in that The heating reaction temperature is 160°C and the time is 12 h, and / or The drying temperature is less than or equal to 80°C.

7. The preparation method according to claim 5, characterized in that In the first solution, the concentration of bismuth nitrate is 0.005-0.5 mmol / mL; in the second solution, the concentration of potassium iodide is 0.005-0.5 mmol / mL.

8. The preparation method according to claim 5, characterized in that During the process of dropwise adding the second solution to the first solution, the molar ratio of the bismuth nitrate to the potassium iodide is controlled to be 1:

1.

9. The preparation method according to claim 5, characterized in that In the process of adding the second solution dropwise to the first solution, controlling the stirring speed to be 400 r / min to 800 r / min and the stirring time to be 5 to 20 min; and / or In the process of dissolving bismuth nitrate in ethylene glycol methyl ether, controlling the stirring speed to be 100 r / min to 500 r / min and the stirring time to be 25 to 60 min; and / or In the process of dissolving potassium iodide in ethylene glycol methyl ether, the stirring speed is controlled to be 100 r / min~500 r / min, and the stirring time is 5~60 min.

10. Use of a core-shell catalyst according to any one of claims 1 to 4, characterized in that: The core-shell catalyst is used to inactivate at least one of algae, pathogenic microorganisms, and degrade pollutants, wherein the pollutants include at least one of phenol, bisphenol A, and antibiotics.

Citation Information

Patent Citations

  • Copper-doped bismuth vanadate-silver iodide activated persulfate photocatalyst as well as preparation method and application thereof

    CN116408110A

  • Preparation method of BiOCl / BiOI composite catalyst for visible light degradation of rhodamine B

    CN119565642A

  • Composite with synergistic effect of adsorption and visible light catalytic degradation and preparation method and application thereof

    US20180008953A1